Geographic Information System of Public Complaint Testing Based On Mobile Web (Public Complaint) - Mahendra, Made Yudha Putra; Piarsa, I Nyoman; Putra Githa, Dwi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 2 August 2018, 2018)
A public complaint is a reciprocal of the population against the government to convey opinions or problems encountered in certain areas. The complaint process using a suggestion box or counter complaint is less effective and efficient so that the complaint handling process is slow. The geographic information system of public complaints is an information system built as an intermediary for the public to make complaints against the government. This public complaint geographic information system is built by utilizing location-based services. Geographic information systems of public complaints that have been built require a test to ensure all functions contained on the system can run properly. This study discusses the testing of the geographic information system of public complaints that have been built by blackbox testing and test by involving respondents from the general public. The results of testing system usage by the user based on aspect of system interface display and conformity aspects of processes and features involving respondents from the general public. Tests conducted to get the average results of respondents gave very good value 28%, good 59.8, enough 10.2% and less by 2%. Comparison of systems conducted on two similar systems taken through a literature study showed that a mobile web-based public complaint geographic information system (Public Complaint) has more features in tracking the location of complaints.